IDENTIFIKASI DAN PEMBOBOTAN RISIKO RANTAI PASOKAN: SEBUAH TINJAUAN LITERATUR - Indrawati, Chatarina Dian (Widya Warta, 2017)
For a manager or manager of an organization, risk is a threat / danger that may interfere with normal activities or stop a thing that has been planned. Risks generally occur in all areas, including the supply chain. The supply chain is the process of linking the process from the initial search of raw material sources or commodities to the stages of manufacturing, processing, storage, transportation to last delivery and consumed by the end consumer. Risk identification is done by qualitative method approach such as literature study, survey / questionnaire / interview with supply chain actors with reference to SCOR, AHP and ANP model, followed by descriptive analysis. From the risk identification result, there is risk taking to determine the priority of risk that is immediately mitigated. The risk-weighted approach is carried out with a quantitative approach such as FMEA, Fuzzy FMEA, FAMs, OWA, AHP, Fuzzy AHP and ANP.